Evaluasi Sistem E-learning Menggunakan Model Hot Fit (Studi Kasus Pada SMKN 1 Tangerang Selatan) - Deni Setiawan; Sewaka (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The 2019 corona virus outbreak has hit 215 countries in the world. To fight (covid-19) the government has prohibited gatherings, therefore the government recommends social distancing, physical distancing, wearing masks and washing hands. Therefore, the ministry of education and culture has forbidden to carry out face-to-face learning, so learning is done online (Firman, F., and Rahayu, S., 2020). E-learning is a learning system that uses electronic applications that allow the delivery of learning materials to students at SMKN 1 Tangerang Selatan using the internet. E-learning is built to make it easier for students to access teaching materials at school without replacing conventional learning methods. Based on these problems, the purpose of this study is to facilitate learning for students, easy to reach for students and teachers to facilitate online learning, with training users can understand how to use E-learning. Based on the results of the problem mapping, the process carried out is. Ensuring satisfaction in an E-learning system and measuring these success factors. Compatible methods for evaluating and implementing E-learning systems in this study are Human, Organization, Technology. The results of this study that satisfaction from several indicators, namely System Quality stated dominant strongly agreed, Information Quality stated dominant strongly agreed, Service Quality stated dominant strongly agreed, System Use stated dominant strongly agreed, User satisfaction stated dominantly agreed, Organizational Structure stated dominantly agreed, Organizational environment stated dominantly agreed, Benefits of E-learning stated dominantly agreed.